Records management practices in Selangor Islamic Religious Council/ Wan Abdul Malek Wan Abdullah ... [et al.] - Wan Abdullah, Wan Abdul Malek; Samsudin, Ahmad Zam Hariro; Masron, Mohd Zairul; Ahmad, Mohd Nazir (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
This study was carried out with the objectives of investigating records management practice in the Selangor Islamic Religious Council (SIRC). Using the survey research methodology, involving 105 personnel attached to 17 agencies under SIRC. The questionnaires incorporated information on records management practices segmented into several sections namely institutionalization; records creation; classification; maintenance and use; selection and acquisition; description of records inventory and finding aids; preservation. The findings of the study indicate that records management practices in SIRC need to be improve to ensure records are managed properly throughout the fife cycle.